APAKAH PERNYATAAN JAMINAN MENINGKATKAN KREDIBILITAS LAPORAN KEBERLANJUTAN? SEBUAH TINJAUAN LITERATUR SISTEMATIS PENELITIAN AKUNTABILITAS PERUSAHAAN - Yudi Basma Albahrun; Muh Faiz Qaidhan Jamsir; Darwis Said; Nadhirah Nagu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study investigates whether and under what conditions assurance on sustainability reports enhances the credibility of information for users. Drawing on a Systematic Literature Review of indexed publications from 2016–2025, we apply PRISMA procedures and complement the thematic synthesis with VOSviewer-based bibliometric mapping of author collaborations and conceptual clusters. The review finds that credibility gains are strongest when assurance design features are explicit: a clearly specified assurance level (particularly reasonable assurance), the use of recognized standards (ISAE 3000/AA1000AS, with increasing convergence toward ISSA 5000), and a materiality-anchored scope supported by substantive procedures. Provider competence and independence further moderate these outcomes. Institutional determinants including long-term institutional ownership, legal system characteristics, and stakeholder pressure also influence adoption. Documented consequences include improved access to finance, more disciplined market reactions, and favorable evaluations in ESG-linked lending. Conversely, narrow scopes, boilerplate phrasing, or limited assurance without transparent methodology tend to weaken credibility effects. Practical implications highlight the need for clearer disclosure of the linkages between assurance level, standards, and scope in executive summaries, enhanced report readability, strengthened thematic expertise among assurance providers, and regulatory alignment to balance costs and benefits. The paper contributes a “design/provider credibility market consequences” mechanism framework and proposes a concise research agenda to guide scholars, practitioners, and policymakers.